2015
DOI: 10.1007/s00253-015-6398-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and immunogenic potential of B cell epitopes of outer membrane protein OmpF of Aeromonas hydrophila in translational fusion with a carrier protein

Abstract: Aeromonas hydrophila, a ubiquitous and virulent bacterial pathogen, affects a variety of fishes, including Labeo rohita. Existing treatment strategies comprise antibiotic therapies and attenuated bacterial strain-based vaccines. No functional subunit vaccine has been available until now. Given their key role in determining pathogenicity, outer membrane proteins have been successfully explored as potential vaccine candidates. We have devised a direct strategy for eliminating non-specific responses by selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…Immunization with OmpF of Yersinia pseudotuberculosis not only resulted in production of high-avidity antibodies, but also stimulated bactericidal activity of peritoneal macrophages (Sidorova et al 2014). Sharma et al suggested that the OmpF epitope (66–80) in fusion with a carrier protein is a promising vaccine candidate against A. hydrophila (Sharma and Dixit 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Immunization with OmpF of Yersinia pseudotuberculosis not only resulted in production of high-avidity antibodies, but also stimulated bactericidal activity of peritoneal macrophages (Sidorova et al 2014). Sharma et al suggested that the OmpF epitope (66–80) in fusion with a carrier protein is a promising vaccine candidate against A. hydrophila (Sharma and Dixit 2015). …”
Section: Introductionmentioning
confidence: 99%
“…columnare DNAk protein? Other studies will need to characterize responding B-cell populations and identify specific epitopes and elucidate whether there is a functional role for F. columnare anti-DNAk antibodies in immunity against columnaris disease (Krska et al, 1993;Sharma and Dixit, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analysis of the agglutination ability of rOmpC antisera with live A. hydrophila cells was performed essentially as described by Sharma et al [19]. Cultures (O/ N) of different bacterial strains were grown at 37°C.…”
Section: Agglutination Assaymentioning
confidence: 99%
“…with two booster doses on day 14 and day 28 of primary immunization. Lymphocyte proliferation assay was performed as described essentially by Sharma et al [19]. Briefly, splenocytes isolated from the spleens of the mice immunized with rOmpC (20 lg/mouse), 7 days post second booster (i.e., on day 35), were treated with chilled ammonium chloride (0.9 %) to lyse the red blood cells.…”
Section: Lymphocyte Proliferation Assay and Cytokine Elisamentioning
confidence: 99%
See 1 more Smart Citation